2012
DOI: 10.1292/jvms.11-0372
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Extended-Spectrum β-Lactamase-Producing Escherichia coli and Klebsiella pneumoniae in Food-Producing Animals

Abstract: ABSTRACT. To evaluate the diversity of extended-spectrum -lactamases (ESBL) genes among food-producing animals, 48 isolates of ESBL-producing Escherichia coli isolates were obtained from rectal samples of broilers, layers, beef cattle and pigs, at the slaughterhouse level. ESBL-carrying E. coli were isolated from 60.0% of individual broiler rectal samples, 5.9% of layers, 12.5% of beef cattle and 3% of pigs. One ESBL-producing Klebsiella pneumoniae was isolated from a broiler. The ESBL-positive E. coli isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
60
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 38 publications
9
60
3
2
Order By: Relevance
“…This is at variance with the results of studies by Hiroi et al and Geser et al, in which layers are recognized as the major reservoir of ESBL-producing E. coli [14,15].…”
Section: Discussioncontrasting
confidence: 90%
“…This is at variance with the results of studies by Hiroi et al and Geser et al, in which layers are recognized as the major reservoir of ESBL-producing E. coli [14,15].…”
Section: Discussioncontrasting
confidence: 90%
“…As shown in Table 2 it was concluded that in diseased cows the highest rate of isolation was obtained from faecal samples (32.1%) followed by nasopharyngeal swabs (28.7%), the lowest incidence could be isolated from milk samples (16.0%). These results agreed to great extent with the finding of Hiroi et al (2012) who isolated Klebsiella pneumoniae from nasal swabs and bronchial mucous collected from calves suffering from bronchopneumonia. Moreover, Munoz et al (2007) reported that Klebsiella pneumoniae had been isolated from faecal samples of diarrhoeic calves.. As regard to sheep samples in this study Klebsiella pneumoniae was mainly predominant in faecal samples, nasopharyngeal swabs and milk samples 40.9, 17.4 and 14.3%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Because the food chain could be a major route of bacterial transmission to humans, we speculated that food-producing animals might also act as reservoirs for these drug-resistant microorganisms in Japan. Some investigations have found that ESBL-producing E. coli have been increasingly isolated from chicken meat samples (7,8). However, epidemiological data describing ESBL-producing E. coli isolated from pigs remain quite limited in Japan.…”
Section: Introductionmentioning
confidence: 99%